Application of Regional Culture Features into the Product Packaging Design to Improve the Traditional Foods Packaging and Enhance Consumers Satisfaction - Ba, Yue; Abidin, Sazrinee Zainal; Shaari, Nazlina; Effendi, Raja Ahmad Azmeer Raja Ahmad (Journal of Ecohumanism, 2024)
Features of regional culture have been considered for application in regional foods packaging design since it can effectively enhance the cultural value of regional traditional foods. This study aims to understand the impact of regional cultural features on regional traditional foods; then analyzing the design approach of application regional cultural features into packaging design on the traditional foods packaging; and finally, exploring the influence of traditional foods packaging design with regional cultural features on consumer satisfaction. The results proposing a conceptual framework for improving the regional traditional foods packaging design to enhance consumer satisfaction. The proposed conceptual framework recommends that by applying the different dimensions of regional cultural features to traditional foods packaging design, designers can design product packaging which helps to enhance the cultural value of the product. This study recommends further research into how packaging design and regional culture promote the image of traditional foods. The results are significant because they will help designers effectively improve regional traditional foods packaging design to enhance consumer satisfaction.